Customer relationship management : concepts and technologies - Buttle, Francis (Routledge<, 2015)
"This much-anticipated new edition of the bestseller Customer Relationship Management provides a comprehensive and balanced review of CRM, now with substantial revisions responding to the recent changes in CRM practice. The book explains what CRM is, the benefits it delivers, the contexts in which it is used, the technologies that are deployed, and how it can be implemented. Both theoretically sound and managerially relevant, the book draws on academic and independent research from a wide range of disciplines including IS, HR, project management, finance, strategy and more. Buttle and Maklan, clearly and without jargon, explain how CRM can be used throughout the customer life cycle stages of customer acquisition, retention and development. The book is illustrated liberally with screenshots from CRM software applications and case illustrations of CRM in practice. NEW TO THIS EDITION: - Updated instructor support materials online - Full colour interior - Brand new international case illustrations from many industry settings - Substantial revisions throughout, including new content on: o Social media and social CRM o Big data and unstructured data o Recent advances in analytical CRM including next best action solutions o Marketing, sales and service automation o Customer self-service technologies o Making the business case and realising the benefits of investment in CRM Ideal as a core textbook by students on CRM or related courses such as relationship marketing, database marketing or key account management, the book is equally valuable to industry professionals, managers involved in CRM programs and those pursuing professional qualifications or accreditation in marketing, sales or service management"--